Enhancing Academic Service Efficiency: Design, Implementation, and Evaluation of a Web-Based Laboratory Booking System Using the Systems Development Life Cycle Framework - Dwipanilih, Rayi; Annisa, Ellis; Ikhwan, Muhammad (Institut Riset dan Publikasi Indonesia, 2025)
This study addresses inefficiencies in higher education administration that hinder the achievement of Sustainable Development Goal 4 (SDG 4), particularly in managing shared academic resources like laboratories. It presents the design, implementation, and evaluation of a web-based laboratory booking system developed using the Waterfall model within the Systems Development Life Cycle (SDLC), utilizing JavaServer Pages (JSP) and MySQL. The system features real-time lab availability tracking, automated booking, and an integrated administrative dashboard. Usability was assessed through quantitative testing and a System Usability Scale (SUS) survey involving 30 participants, including students and lab staff. Results showed a task completion rate above 95% and an average SUS score of 83.6, categorized as “excellent” and within the top usability percentile. The findings demonstrate that a systematically developed web-based solution can substantially enhance administrative efficiency, resource utilization, and user satisfaction. Moreover, the research provides a scalable and replicable model for academic institutions aiming for digital transformation, underscoring that improving operational systems is a critical step toward realizing the goals of quality education and institutional sustainability aligned with SDG 4.